Microgap Evaluation of MTA and RMGIC Orifice Barriers after Nanochitosan-Based Final Irrigation: SEM and Stereomicroscopic Study: Microgap Evaluation of MTA and RMGIC Orifice Barriers - Trimurni Abidin; Zahrah Nabilah; Cut Nurliza; Widi Prasetia (Universitas Syiah Kuala, 2025)
Nanochitosan oligosaccharide has been developed as a final irrigation material, but its effect on leakage of orifice barrier material is not yet known. This study aims to observe the effect of the combination of 2.5% NaOCl + 2% Nanochitosan Oligosaccharide and 2.5% NaOCl + 17% EDTA irrigation on MTA and RMGIC microleakage as orifice barrier materials. A total of 24 extracted mandibular premolars underwent endodontic treatment. Gutta percha was removed vertically to a depth of 2 mm. The tooth samples were divided into four groups, namely, the 2.5% NaOCl + 2% nanochitosan oligosaccharide irrigation group with MTA and RMGIC as barrier materials, and the 2.5% NaOCl + 17% EDTA irrigation group with MTA and RMGIC as orifice barrier materials. After the thermocycling procedure, the samples were immersed in 0.5% Basic Fuchsin solution for 24 hours, then sectioned in the bucco-lingual direction. Dye penetration was measured by two observers using stereomicroscope and scored 0-4. The kappa statistic showed strong agreement between the two observers (p>0.6). The results of microleakage observations showed mean values and standard deviations of group I (1±1.549), group II (3.83±0.408), group III (1.50±1.761), and group IV (3.83±0.408). The Kruskal Wallis test showed significant differences between the four treatment groups (p=0.005). The combination of 2.5% NaOCl + 2% Nanochitosan Oligosaccharide irrigation with MTA resulted in the lowest microleakage